2019
DOI: 10.1051/0004-6361/201834975
|View full text |Cite
|
Sign up to set email alerts
|

The RWST, a comprehensive statistical description of the non-Gaussian structures in the ISM

Abstract: The interstellar medium (ISM) is a complex non-linear system governed by the interplay between gravity and magnetohydrodynamics, as well as radiative, thermodynamical, and chemical processes. Our understanding of it mostly progresses through observations and numerical simulations, and a quantitative comparison between these two approaches requires a generic and comprehensive statistical description of the emerging structures. The goal of this paper is to build such a description, with the purpose to permit an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 70 publications
(89 reference statements)
3
76
0
Order By: Relevance
“…In addition,Ŝ iso,1 2 coefficients for R[Q + iŨ] show a scale invariance property:Ŝ iso,1 2 coefficients only depend on the difference j 2 − j 1 . We point out that these scale invariant patterns are signatures of scale invariant Gaussian processes (Bruna et al 2015) and have already been observed for fractional Brownian motions processes in Allys et al (2019).…”
Section: Second Order Coefficients and Non-gaussianity Of The Datasupporting
confidence: 69%
See 4 more Smart Citations
“…In addition,Ŝ iso,1 2 coefficients for R[Q + iŨ] show a scale invariance property:Ŝ iso,1 2 coefficients only depend on the difference j 2 − j 1 . We point out that these scale invariant patterns are signatures of scale invariant Gaussian processes (Bruna et al 2015) and have already been observed for fractional Brownian motions processes in Allys et al (2019).…”
Section: Second Order Coefficients and Non-gaussianity Of The Datasupporting
confidence: 69%
“…XLII 2016; Ghosh et al 2017;Vansyngel et al 2017;Levrier et al 2018;Adak et al 2020;Clark & Hensley 2019) or directly from numerical simulations (Kim et al 2019). It follows what has been done for dust total intensity by Allys et al (2019) using the RWST, and Aylor et al (2019) using a Generative Adversarial Network.…”
Section: Random Syntheses Ofq + Iũ Polarization Mapsmentioning
confidence: 78%
See 3 more Smart Citations